Annual review of working conditions 2009-2010 - Giaccone, Mario. (Υπηρεσία Επισήμων Εκδόσεων των Ευρωπαϊκών Κοινοτήτων, 2011)
The seventh annual review of the European Working Conditions Observatory (EWCO), which is part of the European Foundation for the Improvement of Living and Working Conditions (Eurofound), summarises the main developments at EU level in the area of working conditions and quality of work and employment during the period February 2009 to January 2010. Divided into five thematic chapters, it explores labour market developments and demographic change, social protection, flexicurity and corporate social responsibility (CSR), working conditions, and equal opportunities.